Promoting Mental Health: The Experiences of Youth in Residential Care - Arsenault, Chelsea L.; Domene, José F. (Canadian Journal of Counselling and Psychotherapy, 2018)
This qualitative study used the enhanced critical incident technique to explore the experiences of youth who are living in residential childcare facilities and identified key influences on their mental health during the transition into adult life. Participants were 8 youth (aged 16 to 18; 6 European Canadian, 2 Aboriginal Canadian) who engaged in individual semistructured interviews. Analyses of transcribed interview transcripts revealed that numerous themes in the areas of internal processes, interpersonal relationships, and impact of social contexts have the potential to influence in unique ways the mental health of youth who are living in residential care.